الذكاء الانفعالي و علاقته باستراتيجيات مواجهة الضغوط المهنية دراسة ميدانية لدى عمال المؤسسة الاستشفائية العقيد لطفي240 سرير بالاغواط - نصيرة بوقرين; فاطنة بوعيشة; كروم خميستي (My University, 2023)
This study aims to find out the relationship between emotional intelligence and the strategy of coping with working pressures in the hospital institution of 240 beds in Laghouat. Knowing the level of emotional intelligence and the strategy for coping with professional pressures. - It also aimed to find out the extent of the differences in emotional intelligence and the strategy of coping with working pressures due to some variables of workers (sex, seniority at work). - This study relied on the descriptive approach, its correlational pattern. - Two scales were adopted in emotional intelligence and the strategy for coping with working pressures, the necessary data collection tool, which was distributed to a sample of 48 male and female workers in the 240-bed Colonel Lotfi hospital in Laghouat. The results of the study revealed the following: • There is a very strong direct relationship between emotional intelligence and coping strategies for working pressures among the workers of the hospital institution Colonel Lotfi 240 Bed Laghouat. • The level of emotional intelligence is high among the workers of the 240-bed hospital colonel Lotfi in Laghouat. • There are statistically significant differences between the degrees of emotional intelligence between the two sexes in favor of males. • There are statistically significant differences between the two genders in the degree of coping strategy for working pressures in favor of males. • There are statistically significant differences in the degree of emotional intelligence between the two categories of seniority in favor of the category of more than 10 years. • There are no differences between the two categories of seniority in the degree of strategy of facing working pressures. Keywords : working pressure , emotional intelligence, strategies to face working pressure.